Learning for a World Changed by Intergenerational Equity - Peter Blaze Corcoran; Philip Molo Osano (Environmental Association of Southern Africa, 2007)
Secure Earth's bounty and beauty for present and future generations. a. Recognize that the freedom of action of each generation is qualified by the needs of future generations. b. Transmit to future generations values, traditions, and institutions that support the long-term flourishing of Earth's human and ecological communities. Earth Charter Principle 4 Intergenerational equity, the ethic of responsibility among generations, is stated in the Earth Charter as the imperative to 'recognize that the freedom of action of each generation is qualified by the needs of future generations' (Earth Charter Commission, 2000:Subprinciple 4.a). Clearly, ethics call out for responsibility to those yet to come of age. Indeed, this is at the heart of sustainable development - to 'meet the needs of the present without compromising the ability of future generations to meet their needs'.1 We believe that 'learning in a changing world' must pay particular attention to the ethical principle of intergenerational equity and to the dramatic demographics of an increasingly youthful population. Second, it presents a powerful opportunity for society if young people can participate in positive aspects of life, such as culture, environment, governance, politics and commerce, to promote sustainable development. In order to do so, young people need the support of older generations in terms of appropriate policies, education, information, financial resources, and hope. Young people have an enormous stake in the present and future state of the planet. For instance, through their lifestyles, they influence commerce and the media industry and shape the process of production, marketing, and consumption patterns of goods and services (UNEP/ UNESCO, 2001). Since young people are also tomorrow's workers, entrepreneurs, parents, and political leaders, the policy makers know that they will greatly influence the future of their nations and global governance (World Bank, 2006).